2017
DOI: 10.1097/brs.0000000000002453
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Ideal Lumbar Total Disc Replacement Patient and Standard of Care

Abstract: : Lumbar total disc replacement, now in use since 2004, was determined by the panel to be a standard of care for the treatment of symptomatic single-level lumbar degenerative disc disease in the active patient subpopulation as outlined by the investigational device exemption study criteria. The large body of evidence supporting this statement, including surgeons' experiences, was presented and discussed. Consensus statements focusing on decision-making criteria reflected that efficacy, long-term safety, clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The soft tissue dissection-wise, endoscopic is least invasive compared to tubular microscopic decompression surgery, which in turn is less invasive than open surgery [161,162]. Total disc replacement is a procedure that involves the removal of the intervertebral disc and replacing it with an artificial disc, which is typically made up of metal and plastic parts that are bioinert and with mechanical properties suitable for spine biomechanics [164,165]. The joint movement is mostly preserved while aiming to take away the pathological disc, leading to pain relief and an increase in the foraminal height.…”
Section: Degenerative Disc Disease With or Without Spinal Stenosismentioning
confidence: 99%
“…The soft tissue dissection-wise, endoscopic is least invasive compared to tubular microscopic decompression surgery, which in turn is less invasive than open surgery [161,162]. Total disc replacement is a procedure that involves the removal of the intervertebral disc and replacing it with an artificial disc, which is typically made up of metal and plastic parts that are bioinert and with mechanical properties suitable for spine biomechanics [164,165]. The joint movement is mostly preserved while aiming to take away the pathological disc, leading to pain relief and an increase in the foraminal height.…”
Section: Degenerative Disc Disease With or Without Spinal Stenosismentioning
confidence: 99%
“…Total disc replacement (TDR) has less of a risk of ASD compared with fusion surgeries; however, there are known risk factors including heterotopic ossification and the risk of reoperation. TDR is best indicated in spinal levels (eg, cervical) where maintained mobility is of greater importance . Percutaneous endoscopic or minimally invasive tubular decompressive surgeries are also widely performed; good clinical results have been reported in selected patients with a localized lesion and IVD herniation .…”
Section: Available Clinical Treatments For Discogenic Painmentioning
confidence: 99%
“…TDR is best indicated in spinal levels (eg, cervical) where maintained mobility is of greater importance. (93)(94)(95)(96)(97) Percutaneous endoscopic or minimally invasive tubular decompressive surgeries are also widely performed; good clinical results have been reported in selected patients with a localized lesion and IVD herniation. (98)(99)(100) However, obtaining successful clinical outcomes for treating discogenic LBP with these surgical measures have been challenging.…”
Section: Available Clinical Treatments For Discogenic Painmentioning
confidence: 99%
“…This has provoked patients and spine surgeons, and there has been debate on the reason for this practice [324]. In a report from the First Annual Lumbar TDR Summit in 2016 [325], consensus statements included that reliable tools exist for identifying patients with discogenic back pain [326], sufficient data are available for the long-term efficacy and safety of TDR [223] and the cost to US health insurers were expected to remain unchanged if coverage for lumbar TDR were provided [324]. The future role of TDR is difficult to predict, but in a recent systematic review of 59 clinical trials, Formica et al [206] concluded that it could be a reliable option for the treatment of LBP in patients with IDD in years to come.…”
Section: Future Perspectivesmentioning
confidence: 99%